A Comparative Study of I.C.S.E., C.B.S.E. and U.P. Board Students regarding Comprehension of Environmental Issues - Awasthi, Malini; Agarwal, Reena (JOURNAL OF INDIAN EDUCATION, 2013)
In the present education system aspects of environmental concerns are introduced in the curriculum in various ways. Children in the school are gaining knowledge and understanding of environmental issues through textbooks, projects and various activities. We need to find out that to what extent the basic knowledge and understanding of various issues of environmental concerns have been imbibed by school children. A comparative analysis of the comprehension regarding different aspects of environmental concerns in students studying in schools affiliated to different Boards of education highlights the positive aspects and the weakness in the environmental education curriculum being followed by these schools. It will help in identifying major areas which need to be worked on for the better understanding of environmental concerns among students. Since environmental concern is a very broad area and various aspects are interlinked with each other, hence students’ understanding could only be developed if they are able to establish if-then and cause-effect relationship between various aspects of environmental concerns.